The Effectiveness of Socioscientific Issue-Based Petroleum Materials Integrated with The Elsmawar Website on Students’ Scientific Literacy - Indang Dwi Rahayu; Anna Permanasari; Leny Heliawati (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to determine the effectiveness of Socioscientific Issue (SSI)-based petroleum materials integrated with the eLSMAWAR website on students’ scientific literacy during the COVID-19 Pandemic. However, it still targets the achievement of 21st-century skills, namely scientific literacy competencies. Scientific literacy is needed as a skill that can answer the demands of the 21st-century era, as a problem solver that is competitive, innovative, creative, collaborative, and has character. This research method uses Research and Development (R D), which refers to Borg and Gall’s development model. The instrument used in this study was an expert validation sheet filled in by a validator which was useful for knowing whether it was feasible or not to develop. Students are given ten descriptive questions on a 1-4 Likert scale to determine the effect of teaching materials on scientific literacy. The data obtained were analyzed by descriptive quantitative. Expert validation resulted in an average percentage of 87% on material, presentation, language, and legibility aspects. For the validation of chemistry educators, the mean score of CVI for the language aspect and legibility is 0.80; the material aspect is 0.86; for the presentation, aspect is 0.84. This means that based on chemistry experts and educators, the criteria for SSI-based petroleum materials integrated with the eLSMAWAR website are appropriate/valid and very suitable for use. The scientific literacy test results obtained an N-Gain of 0.66, which means that the SSI-based teaching materials integrated with the eLSMAWAR website are quite effective in improving students’ scientific literacy. The research concludes that the teaching material based on Socioscientific Issue (SSI) integrated with the eLSMAWAR website on students’ scientific literacy with three indicators of scientific literacy is following the demands of the implementation of 21st-century skills.